Consumption in Environmental Education: Developing Curriculum that Addresses Cradle to Cradle Principles (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
The body of literature on ‘responsible’, ‘ethical’, or ‘green’ consumption, as well as barriers to it, has been growing (for a recent reviews and case study of barriers to sustainable consumption, see Kollmuss and Agyeman, 2002 and Isenhour, 2010). Recentresearch suggested that the contemporary emphasis on green consumerism might also be driving more consumption as they aim to absolve consumers of their guilt by offering ‘responsible’ products (Zizek, 2011). Scholars have also warned of the ‘‘rebound effect’’(Greening et al., 2000), when consumers rationalize buying ‘green’, ‘ecological’ etc. products advertised by companies expert in the art of green washing marketing. As environmental educators struggle to integrate ‘responsible’ consumption into the school curriculum, questions related to what is ‘responsible’ consumption and how it can be best achieved remain. Based on the distinction between private and public sphere environmentalism (Stern, 2000).